2011
DOI: 10.1371/journal.pone.0024160
|View full text |Cite
|
Sign up to set email alerts
|

From Where Are Tuberculosis Patients Accessing Treatment in India? Results from a Cross-Sectional Community Based Survey of 30 Districts

Abstract: BackgroundTuberculosis (TB) notification in India by the Revised National TB Control Programme (RNTCP) provides information on TB patients registered for treatment from the programme. There is limited information about the proportion of patients treated for TB outside RNTCP and where these patients access their treatment.ObjectivesTo estimate the proportion of patients accessing TB treatment outside the RNTCP and to identify their basic demographic characteristics.MethodsA cross sectional community-based surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
143
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(152 citation statements)
references
References 10 publications
2
143
0
Order By: Relevance
“…Patients were unaware and not informed by providers about the possibility of TB as a diagnosis for their symptoms. As previously reported [17], there was a preference of private providers. In India, there is large prevalence of private providers, and the healthcare costs in private care are higher than in the public sector [17,18].…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Patients were unaware and not informed by providers about the possibility of TB as a diagnosis for their symptoms. As previously reported [17], there was a preference of private providers. In India, there is large prevalence of private providers, and the healthcare costs in private care are higher than in the public sector [17,18].…”
Section: Discussionmentioning
confidence: 56%
“…As previously reported [17], there was a preference of private providers. In India, there is large prevalence of private providers, and the healthcare costs in private care are higher than in the public sector [17,18]. Qualitative interviews revealed that a lack of awareness of TB care service availability in the public sector combined with a lack of awareness about TB symptoms, in the underlying milieu of general preference for private facility, the factors including timings of service availability, perception of quality, etc., could have led to this phenomenon of a higher proportion of participants seeking private-sector care.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…A subset of the data from these surveys was used to answer some specific research questions that were operationally relevant. These studies were written-up as separate manuscripts (n = 6) and published in peer-reviewed journals [1318]. The findings were also presented at The Union’s World Conferences on Lung Health (years 2011–2016).…”
Section: Surveys and Other Project Axshya Activities Related Operatiomentioning
confidence: 99%
“…A publication from the baseline knowledge, attitude and practice survey showed that nearly half of the TB patients in the community were being treated in the private sector, outside the RNTCP notification system [13]. The quality of TB care in the vast un-regulated private sector was largely unknown.…”
Section: Contribution Of or To Policy And Practicementioning
confidence: 99%